USING LEARNING VECTOR QUANTIZATION METHOD FOR AUTOMATED IDENTIFICATION OF MYCOBACTERIUM TUBERCULOSIS - Purwanti, Endah; Widiyanti, Prihartini (Institute of Topical Disease, 2012)
In this paper, we are developing an automated method for the detection of tubercle bacilli in clinical specimens, principally theÂ sputum. This investigation is the first attempt to automatically identify TB bacilli in sputum using image processing and learning vectorÂ quantization (LVQ) techniques. The evaluation of the learning vector quantization (LVQ) was carried out on Tuberculosis datasetÂ show that average of accuracy is 91,33%.